A New Method Linking the Solar Wind Speed to the Coronal Magnetic Field - Casti, Marta; Arge, Charles N.; Bemporad, Alessandro; Pinto, Rui F.; Henney, Carl J. (The Astrophysical journal, 2023)
The release and acceleration of the solar wind is still an outstanding question. There are several aspects related to this phenomenon that still need to be investigated, and one of these is the identification of the region within the inner corona where the larger fraction of acceleration occurs. To address this matter, it is necessary to have reliable measurements of the solar wind speed between 1 and 10 solar radii ( R ⊙ ). Moreover, in order to describe the coronal plasma behavior, it is important to consider its interaction with the magnetic field. Within this context, our intent is to investigate a method to combine measurements of the solar wind with the extrapolated magnetic field in the corona to derive how the solar wind velocity evolves along the magnetic field lines, aiming at better understanding the sources, origins, and acceleration of the solar wind. To this purpose, we used outflow speed measurements of the coronal plasma derived by applying the Doppler dimming technique, as well as the global magnetic field configuration derived from the measured photospheric magnetic field by using the Wang–Sheeley–Arge model. These two sets of data are then combined for heliocentric distances between 2.6 and 5 R ⊙ . This paper presents the proposed method and the results obtained over two different Carrington rotations (CR 1923 and CR 1924), demonstrating the applicability of the method and the capability to link measured solar wind velocity to the extrapolated coronal magnetic field in order to derive the velocity profile.